2017
DOI: 10.15406/atroa.2017.03.00061
|View full text |Cite
|
Sign up to set email alerts
|

Male Sexual Disorders in Patients with Parkinson Disease: Treatment with Natural Remedies

Abstract: In patients with PD, sexual disorders usually begin after the onset AbstractParkinson's disease (PD) is a neurodegenerative disorder caused by a progressive deterioration of midbrain dopamine neurons in the substantia nigra. The incidence of PD in male is higher than that in women, but psychological symptoms are as varied as the motor symptoms in both gender. Psychological symptoms encompass a decrease in sexual desire with a long list of thymic, cognitive, behavioral, and neuropsychiatric complications. Thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Pharmacotherapy and psychoactive drugs in the last two decades have gain recognitions, due to its efficacy in the management of neurological related disorders. However, several studies have revealed that such relieve are temporal with manifestation of various side effects (Handa, 1995;Mireille et al, 2017). Traditional medical practice has gained interest in the world over due to the wide spread usage of medicinal plants and its consumption, especially in developing countries (Ashafa and Olunu, 2011;Sujith et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacotherapy and psychoactive drugs in the last two decades have gain recognitions, due to its efficacy in the management of neurological related disorders. However, several studies have revealed that such relieve are temporal with manifestation of various side effects (Handa, 1995;Mireille et al, 2017). Traditional medical practice has gained interest in the world over due to the wide spread usage of medicinal plants and its consumption, especially in developing countries (Ashafa and Olunu, 2011;Sujith et al, 2012).…”
Section: Introductionmentioning
confidence: 99%